2009
DOI: 10.1007/s12544-009-0008-3
|View full text |Cite
|
Sign up to set email alerts
|

Drive-style emissions testing on the latest two Honda hybrid technologies

Abstract: Introduction Hybrid technology is seen by many as a potential solution to reduce vehicle emissions in cities. However type approval tests of hybrid vehicles measure emission levels comparable to those of conventional cars in the same market segment. It has been argued that type approval tests do not represent the reality of emission in cities therefore, to quantify the real emission of hybrids and to compare them with those of conventional vehicles in the same conditions, an emission measurement campaign was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Two main aspects of tactical behaviour were reviewed: driver aggressiveness and eco-friendliness. Studies showed that aggressiveness and ecofriendliness are interrelated, though not identical (Alessandrini et al, 2009;Sivak, M. & Schoettle, 2012). Some smartphone applications were developed for improving tactical driving behaviour 8,9 .…”
Section: Driver Aggressiveness Classificationmentioning
confidence: 99%
“…Two main aspects of tactical behaviour were reviewed: driver aggressiveness and eco-friendliness. Studies showed that aggressiveness and ecofriendliness are interrelated, though not identical (Alessandrini et al, 2009;Sivak, M. & Schoettle, 2012). Some smartphone applications were developed for improving tactical driving behaviour 8,9 .…”
Section: Driver Aggressiveness Classificationmentioning
confidence: 99%
“…However, logging of powertrain values can also be needed (e.g. rpm, speed, throttle position, engine parameters if ICE, battery/inverter/powertrain parameters if EV or HEV) especially in the case that the aim is to correlate emissions (directly measured at tailpipe) and driving style (Alessandrini et al, 2009) or to correlate traction power to probability of occurrence (Shankar et al, 2012). The availability of logging capabilities through cheap and wide diffusion devices such as car infotainment system and smartphones highlights new possibilities for the monitoring of driving attitudes (Gerardo and Lee, 2009); such data can be used for driver training through continuous learning (Beusen et al, 2009;Corcoba Magana and M unoz-Organero, 2011;Manzoni et al, 2010), thus promoting safe or fuel-saving driving styles.…”
Section: ----Signal Acquisition and Treatment Signal Acquisition And Treatment Signal Acquisition And Treatment Signal Acquisition And Trmentioning
confidence: 99%
“…The relationships between fuel use, emissions and VSP are reflected in the latest EPA regulatory model for mobile source emissions, MOVES, which uses VSP and vehicle speed to forecast emissions from the on-road vehicle fleet. 10 Laboratory measurements of fuel consumption from various model HEVs have shown a dependency on HEV technology, 40 drive cycle 11,41 and ambient temperature. 11,14,42,43 For example, HEVs showed up to three times higher fuel consumption for aggressive, stop-and-go drive cycles compared to highway driving.…”
Section: ■ Introductionmentioning
confidence: 99%
“…44 Thus, HEVs offer up to two times the fuel consumption improvement compared to gasoline CVs, and HEV fuel consumption varies with operating mode. Four prior studies (See Supporting Information (SI) Table S-1) compared the performance of CV to HEV, 11,14,40,44 but each of these studies had shortcomings that do not enable quantification of HEV benefits that can be used for modeling any type of real-world driving. These shortcomings included: (i) the compared CV was of different make/model/model year or aerodynamics; 11,44 (ii) compared CV was manual transmission 40 and thus too dependent on driver behavior; and (iii) comparative analysis was only conducted at the trip or full drive-cycle level and therefore not amenable to quantifying HEV benefit as a function of operating modes such as those based on VSP.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation